The Spiritual Leadership of Dr. Jaiphet Klajon and the Management of Health through the Self-reliant Health learning Center According to the Sufficiency Economy - Sohap, Sudjai; Kangsadarnporn, Korn (Journal of Dhamma for Life, 2025)
This qualitative research aimed to: (1) explore Dr. Jaiphet Klajon’s health management philosophy through the Self-Reliant Health Learning Center guided by the Sufficiency Economy Philosophy, (2) examine the outcomes of health management at the center, and (3) present the spiritual leadership of Dr. Jaiphet Klajon. Data were collected through in-depth interviews with Dr.Jaiphet Klajon and volunteers of the Natural Way of Medicine network. The findings revealed that Dr. Jaiphet Klajon’s concept emphasizes self-reliant living based on natural principles to promote well-being, household stability, and sustainable communities. The outcomes of the center’s practices include self-treatment of illnesses, improved health, reduced defilements, development of volunteer networks and leadership skills, and reduced household expenses. Dr.Jaiphet Klajon’s spiritual leadership is characterized by a clear vision, moral integrity, trustworthiness, compassionate care, and a model of virtuous living. These attributes led to transformations in five areas: health, economy, society, wisdom, and the emergence of a social innovation—self-reliant health based on Natural Way of Medicine. In conclusion, Dr.Jaiphet Klajon’s spiritual leadership aligns with the Sufficiency Economy Philosophy and should be promoted as a model for public health initiatives and community empowerment.